Primary uterine angiosarcoma: A case report in China with the literature review - Liang, Dongni; Li, Lei; He, Yanmei; Jiang, Wei (Indian journal of pathology & microbiology, 2020)
Primary uterine angiosarcoma is a very rare malignant tumor in the female genital tract and only 23 cases have been previously reported in the literature. It is often clinically misrecognized as another disease due to its low incidence. In this report, we present a new case of a 78-year-old woman diagnosed on histopathologic observation and immunohistochemical staining. Additionally, available studies are collected and reviewed to summarize the clinical and pathological characteristics of primary uterine angiosarcoma to remind gynecologists and pathologists of this rare disease when they encounter such cases.